Frege: Una estipulación viable - Lourdes Valdivia (Crítica)
These two objects [The True and the False] are recognized, if only implicitly, by everybody who judges something to be true —and so even by a sceptic. (Frege, G., “On Sense and Reference”, Trans. Geach & Black, p. 63.)